2023
DOI: 10.1002/pon.6094
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effectiveness and implementation of patient treatment decision‐aid tools for men with localised prostate cancer: A systematic review

Abstract: Objective Men diagnosed with localised prostate cancer (LPC) often face a difficult process deciding on a treatment choice that suits their personal preferences. This systematic review examines the impact of patient treatment decision‐aids (DAs) on decisional outcomes and treatment choice for men diagnosed with LPC. Our secondary aim was to examine how DAs have been implemented into routine clinical practice. Methods A systematic search was conducted up to June 2022 using the following databases: Medline, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…DAs have been shown to improve knowledge, risk perception accuracy, congruence between values and choices, patient–clinician communication and decisional involvement and satisfaction and decrease decisional conflict and the uptake of unnecessary surgery across treatment and screening settings 14 . A recent systematic review of DAs designed specifically to support treatment decisions in PC concluded that, while DAs appear to increase knowledge, findings regarding decisional conflict, regret and satisfaction, decisional involvement and treatment choices vary from no impact to only modest effects, highlighting some shortcomings of existing DAs 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAs have been shown to improve knowledge, risk perception accuracy, congruence between values and choices, patient–clinician communication and decisional involvement and satisfaction and decrease decisional conflict and the uptake of unnecessary surgery across treatment and screening settings 14 . A recent systematic review of DAs designed specifically to support treatment decisions in PC concluded that, while DAs appear to increase knowledge, findings regarding decisional conflict, regret and satisfaction, decisional involvement and treatment choices vary from no impact to only modest effects, highlighting some shortcomings of existing DAs 15 …”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to develop an online treatment decision aid (OTDA) for Australian men with LRPC and their partners, titled Navigate . While several OTDAs for LRPC currently exist, these have most often been developed in the United States and the Netherlands 15 . Treatment decisions are inevitably made with reference to the patient's own personal and medical context, including the specific local healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…2 A recent review evaluated 21 different decision aids for men with localized prostate cancer, varying in presentation and format, with most being designed as computer/Web-based multimedia programs, a few as booklets, and some in video format. 3…”
mentioning
confidence: 99%
“…2 A recent review evaluated 21 different decision aids for men with localized prostate cancer, varying in presentation and format, with most being designed as computer/Web-based multimedia programs, a few as booklets, and some in video format. 3 Previous evaluation studies of finalized decision aids-a recent Cochrane review of 105 randomized trials would be an excellent example-have been mainly quantitative: researchers compare endpoints such as treatment choices, decisional conflict, or decisional regret. 4,5 The literature is far sparser for qualitative studies of postprocess evaluation of how patients feel about the tool.…”
mentioning
confidence: 99%
“…See a recent review examining the effectiveness and implementation of patient treatment DA tools for men with localized prostate cancer for further evaluation. 14 The Navigate DA Web site was created to assist Australian men with LPC make informed decisions about their treatment. 15 Navigate was co-designed by a multidisciplinary team and consumers, is theoretically driven, and complies with the International Patient Decision Aid Standards (IPDAS).…”
mentioning
confidence: 99%